Investigation of determinants of stress in patients requiring endodontics therapy: stress in patients requiring endodontics therapy - Hajihassani, Neda; Emrani, Reza; Mohammadhassani, Faeze (Journal of Dental School, 2023)
Abstract: Objectives: Dental stress is often considered as one of the important factors related to the patient's avoidance of dental visits. Considering the lack of comprehensive studies in this regard in Iran, we decided to design a study to explore the causes of dental stress. Material and Method: The DASS (Depression-Anxiety-Stress Scale) was used for data collection. The first part of the questionnaire was related to demographic characteristics, including age, sex, education level and occupation and dental treatment experience. The second part included 21 questions related to the stress. The relationship between the score of questionnaire and psychological and demographic factors were analyzed. Result: Two hundred and fifty-eight patients completed the questionnaires (129 men,129 women). the highest age frequency was seen in the 21-30-year-old group (n=93). The mean age of the patients was 32 years old. women had higher stress scores (p=0.054), First timers had higher mean score to patients with a positive history of dental visit or endodontics treatment (p=0.03). level of education was no related to the stress score. Stress level had negative correlation with age (p=0.03) Conclusion: Demographic and psychological factors are related to the stress. It's necessary to know the cause of stress in dentistry to have a better control on patient and better treatment procedure.